Pentecostalism and human rights in contemporary Zimbabwe - Machingura, Francis; Togarasei, Lovemore; Chitando, Ezra (Cambridge Scholars Publishing, 2018)
"This volume offers updated accounts of Pentecostalism in Zimbabwe, and explores most of the dominant themes in contemporary Pentecostalism, including leadership, competition, gender, youth and prosperity. In addition, some chapters investigate emerging themes in studies on Pentecostalism, such as disability. Contributors to this volume situate Zimbabwean Pentecostalism within the larger continuum of global Pentecostalism, and reflect on Pentecostal biblical interpretation, the interface between Pentecostalism and African Traditional Religions, the use of titles in Zimbabwean Pentecostalism and Pentecostalism's engagement with HIV/AIDS. The book will appeal to scholars in religious studies and theology, religious education, disability studies, social sciences, history, political science, development studies, gender, cultural studies, and anthropology, as well as general readers."--